Perception of Smile Esthetics by Orthodontists and Laypersons: Full Face and A Localized View of The Social and Spontaneous Smiles - Furkan Dindaroğlu; Aslıhan M. Ertan Erdin; Servet Doğan (Galenos Yayinevi, 2016)
Objective:The aim of the study was to evaluate the parameters that might affect the esthetic perception of localized and full-face views of social and spontaneous smiles.Methods:Video records of 40 individuals were used. Further, 200 images of each individual were captured for social and spontaneous smiles with and without calibration glasses. Full-face images of social smile (SSF) and spontaneous smile (smile of joy) (JSF) were obtained. Furthermore, the mouth-area images of the same social (SSM) and spontaneous (JSM) smiles from each subject were acquired. Here 160 images were evaluated by orthodontists and laypersons using the Q-sort method. The data were analyzed with logistic regression and independent samples t-test.Results:From the orthodontic perspective, upper lip thickness (p=0.004), lip curtain over incisors (p=0.016), maxillary incisor display (p=0.01), and buccal corridor ratio (p=0.006) were significant to determine attractive and unattractive images when viewing localized social smiles. Laypersons identified no particular parameter to explain the variation in preferences for all the image groups (p>0.05).Conclusion:Upper lip thickness and maxillary incisor display during smiling were found to be effective for distinguishing images as attractive and unattractive by orthodontists. No objective evaluations for the attractiveness were made by laypersons.